Hubungan Asupan Zat Gizi Makro dan Status Gizi dengan Kebugaran Jasmani Atlet Cabang Olahraga Permainan - Fitrah, Fadlilah Naila; Putriningtyas, Natalia Desy (Jurnal Gizi, 2024)
Background: Physical fitness is a person ability to carry out physical activities. Physical fitness is very important for athletes to improve athlete performance and athlete quality. Sports with aerobic and anaerobic systems require cardiovascular endurance (VO2 max). Physical fitness will run well with adequate energy and macronutrient intake.  Objectives: This study aims to determine the relationship between energy intake, macronutrients and nutritional status with the physical fitness (VO2 Max) of athletes in gaming sports at BPPLOP Central Java.  Method: The research was conducted using analytical observation with a cross sectional design. The research sample was 47 people using a total sampling technique. Data on athletesmacronutrient intake uses the 3x24 hour food recall method, physical fitness (VO2 max) measurements use the bleep test. Data analysis was carried out using the Pearson Correlation Test.  Results: The results of the Pearson correlation test showed that there was no significant relationship between energy intake (p=0.921 R=-0.015), protein (p=0.276 R=-0.162), fat (p=0.778 R=-0.042), and carbohydrates (p= 0.923 R=0.015) on athletes' physical fitness (VO2 max).  Conclusion: It was found that there was a significant relationship between nutritional status (p=0.021 R=-0.335) and physical fitness (VO2 max) of game sports athletes at BPPLOP CentralJava.Key words : carbohydrates, energy, nutritional status, physical fitness (VO2 Max), protein